2019
DOI: 10.3390/sym11030296
|View full text |Cite
|
Sign up to set email alerts
|

Center-Emphasized Visual Saliency and a Contrast-Based Full Reference Image Quality Index

Abstract: Objective image quality assessment (IQA) is imperative in the current multimedia-intensive world, in order to assess the visual quality of an image at close to a human level of ability. Many parameters such as color intensity, structure, sharpness, contrast, presence of an object, etc., draw human attention to an image. Psychological vision research suggests that human vision is biased to the center area of an image and display screen. As a result, if the center part contains any visually salient information, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This bias is widely used in SRD, but is rare in image-quality estimation. Layek et al [66] propose an image quality metric that uses visual saliency and contrast, and extra attention is paid to the center by increasing the sensitivity of the similarity maps between the reference image and the distorted image. In their study, an image is splitted into 3 × 3 blocks, as shown in Figure 2D, and, to enhance the prediction performance, not only the center region but also its whole image are quantified from saliency similarity and contrast similiarty.…”
Section: Discussionmentioning
confidence: 99%
“…This bias is widely used in SRD, but is rare in image-quality estimation. Layek et al [66] propose an image quality metric that uses visual saliency and contrast, and extra attention is paid to the center by increasing the sensitivity of the similarity maps between the reference image and the distorted image. In their study, an image is splitted into 3 × 3 blocks, as shown in Figure 2D, and, to enhance the prediction performance, not only the center region but also its whole image are quantified from saliency similarity and contrast similiarty.…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed algorithm was compared to several state-of-the-art FR-IQA metrics, including SSIM [12], MS-SSIM [14], MAD [49], GSM [56], HaarPSI [20], MDSI [57], CSV [58], GMSD [19], DSS [59], VSI [60], PerSIM [61], BLeSS-SR-SIM [62], BLeSS-FSIM [62], BLeSS-FSIMc [62], LCSIM1 [40], ReSIFT [63], IQ(L T ) [28], MS-UNIQUE [64], RVSIM [65], 2stepQA [66], SUMMER [67], CEQI [68], CEQIc [68], VCGS [69], and DISTS [70], whose original source code are available online. Moreover, we reimplemented SSIM CNN [41] in MATLAB R2019a (Available : https://github.com/Skythianos/ SSIM-CNN).…”
Section: Comparison To the State-of-the-artmentioning
confidence: 99%
“…Our proposed algorithm was compared to several state-of-the-art FR-IQA metrics, including SSIM [12], MS-SSIM [14], MAD [46], GSM [53], HaarPSI [20], MDSI [54], CSV [55], GMSD [19], DSS [56], VSI [57], PerSIM [58], BLeSS-SR-SIM [59], BLeSS-FSIM [59], BLeSS-FSIMc [59], LCSIM1 [39], ReSIFT [60], MS-UNIQUE [61], RVSIM [62], 2stepQA [63], SUMMER [64], CEQI [65], CEQIc [65], VCGS [66], and DISTS [67], whose original source code are available online. Moreover, we reimplemented SSIM CNN [40] in MATLAB R2019a 1 .…”
Section: Comparison To the State-of-the-artmentioning
confidence: 99%